Implementasi Model Manajemen Kelas Efektif dalam Konteks Pendidikan Islam (Studi Kasus di Madrasah Ibtidaiyah Sabilul Muttaqin Pungging Mojokerto): Implementation of Effective Classroom Management Models in the Context of Islamic Education (A Case Study at Madrasah Ibtidaiyah Sabilul Muttaqin Pungging Mojokerto) - syafa'at, wahyu (An-Najmu: Jurnal Manajemen Pendidikan Islam, 2024)
This study aims to investigate the implementation of effective classroom management models in the context of Islamic education, focusing on Madrasah Ibtidaiyah Sabilul Muttaqin in Pungging, Mojokerto. This madrasah is a formal institution based on pesantren, which integrates educational activities with pesantren activities. The research method used is a case study with a qualitative approach. Data were collected through observation, interviews, and documentation studies. The results of the study indicate that the implementation of effective classroom management models at Madrasah Ibtidaiyah Sabilul Muttaqin has improved the conditions of learning, created a conducive environment, and enhanced the quality of education. The conclusion of this study is that an effective classroom management model is crucial in improving the quality of education in pesantren-based madrasahs.